Case Report: Primary Bilateral Minimally Invasive Adenocarcinoma of the Lungs in an 11-Year-Old Child: A Rare Case - Lei, Xing; Zheng, Yongfei; Zhang, Guohua; Zheng, Hailan (Frontiers in Surgery, 2021)
There are many types of benign and malignant tissue, but primary lung tumor is very rare in children and often remains undiagnosed until after distant metastasis has occurred. Few cases of early lung adenocarcinoma in children have been reported. However, this case concerns an 11-year-old child with primary bilateral minimally invasive adenocarcinoma. As far as we know, this is the youngest reported case of its type.